Action of cilostazol in diabetic and non-diabetic rats as prevention of atherosclerosis (Research, Society and Development, 2023)
Atherosclerosis is a chronic inflammatory disease of multifactorial origin that occurs in response to endothelial aggression, affecting mainly the intimal layer of medium and large arteries. Type 2 diabetes mellitus is associated with a high rate of atherosclerotic cardiovascular disease. This study aims to analyze the impact, by drug treatment of Cilostazol, which is an antiplatelet drug, on the reduction of the aortic artery thickness of rats induced to develop diabetes through the administration of streptozotocin, compared to a control group without diabetes. The study showed that the time it took for the rat to develop diabetes was 8 weeks, the rats in the group that was administered streptozotocin showed a significant increase in aortic arterial thickness, especially in the intimal layer of the artery. A reduction in the thickness of the intimal layer of the aorta arteries of the rats submitted to treatment with cilostazol was observed, with significant significance when comparing the groups with diabetes and even when comparing the rats that were not induced to diabetes, showing that cilostazol can be a great ally in preventing atherosclerosis.